Site-specific microinjection of Gaboxadol into the infralimbic cortex modulates ethanol intake in male C57BL/6J mice - Fritz, Brandon M. (2014)
Extrasynaptic GABA(A) receptors, often identified as those containing both α4 and δ subunits, demonstrate super-sensitivity to GABA and are involved in tonic inhibitory processes regulating activity within mesolimbocortical circuitry. Rodent studies testing the effects of the δ-subunit selective agonist Gaboxadol (THIP) on alcohol consumption have produced mixed results. The goal of this study was to determine the role of extrasynaptic GABA(A) receptors located in the infralimbic cortex (ILC) in the alcohol consumption of male C57BL/6J (B6) mice. The ILC is of interest due to its demonstrated involvement in stress reactivity. Furthermore, alcohol exposure has been shown to interfere with extinction learning; impairments of which may be related to inflexible behavior (i.e. problematic alcohol consumption). Adult male B6 mice were bilaterally implanted with guide cannulas aimed at the ILC and were subsequently offered daily limited access to 20% ethanol or 5% sucrose for 7 days. Immediately prior to ethanol or sucrose access on day 7, mice were bilaterally injected with 50 or 100 ng THIP (25 or 50 ng per side respectively) or saline vehicle into the ILC. The highest dose of intra-ILC THIP (100 ng/mouse) increased alcohol intake relative to vehicle controls, although control animals consumed relatively little ethanol following infusion. Intra-ILC THIP had no effect on sucrose consumption (p > 0.05), suggesting that the effect of THIP was selective for ethanol consumption. Together, these findings suggest that THIP may have effectively prevented the decrease in ethanol intake on day 7 induced by the microinjection process, perhaps supporting a suggested role for the ILC in adaptive learning processes and behavioral flexibility.